The Importance of Genetic Testing in the Diagnosis of Parkinson’s Diseas - Dakinevičiūtė, Dominika; Čičelienė, Jolita (Neurologijos seminarai, 2024)
Background. Parkinson’s disease is a common neurodegenerative disorder which causes various motor, autonomic, and cognitive disorders affecting the patient’s quality of life. The etiology of the disease is multifactorial, as Parkinson’s disease is associated with both environmental and genetic factors. The interaction between these two aspects is important. Parkinson’s disease is diagnosed based on clinical criteria, and instrumental studies, such as MRI, PET, SPECT, or CT, can be used for differential diagnosis. Currently, genetic testing is not widespread in the clinical practice, but it may play a significant role in the future, not only by serving as a prognostic or diagnostic indicator, but also by helping in selecting effective, genetically oriented treatment for Parkinson’s disease.Materials and methods. A scientific literature review was conducted, and publications were gathered from PubMed (MEDLINE), ScienceDirect (Elsevier), Google Scholar, and UpToDate electronic databases using keywords and their combinations. The literature review included publications in English published from 2018 to 2023.Results. It is known that over 20 genes are associated with the manifestation of Parkinson’s disease. SNCA, VPS35, PRKN, LRRK2, PINK1, and DJ1 genes are most frequently mentioned in the literature. The penetrance of these genes varies, being either low or high, in terms of influencing the probability of disease occurrence. Mutations in the GBA gene represent the most commonly found genetic factor in Parkinson’s disease. Genetic testing for Parkinson’s disease is not commonly used in the routine clinical practice, but it should be considered on an individual basis. Currently, it is possible to test all the known genes that are associated with Parkinson’s disease, although two genes that are most commonly tested are LRRK2 and GBA. As new treatment methods for Parkinson’s disease related to gene therapy are emerging, genetic testing discussions will become increasingly relevant.Conclusions. Parkinson’s disease is associated with numerous risk factors, and the genetic factors depend on gene penetrance. Genetic testing is not standard in the current clinical practice, but it may gain significant importance in the future.
Keywords: Parkinson's disease; genetic testing